Gigon/Guyer's steel-shingled : Liner Museum glimmers against the sloping farmlands of Appenzell, Switzerland - Amelar, Sarah
Sobre Liner Museum de Gigon/Guyer.
Keywords: GIGON / GUYER ARCHITEKTEN; GIGON, ANNETTE; GUYER, MIKE; SUIZA